VISUALISASI PERSEBARAN OBAT MENGGUNAKAN VISUAL DATA MINING (VDM) STUDI KASUS PADA PT. BERNOFARM WILAYAH LAMPUNG - Yoshua, Gregorius; Apsiswanto, Untoro (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Data visualization is a general term that describes any attempt to help people understand the significance of data by placing data in a visual context. Although it may seem simple, there are many benefits to visualizing data, from making data easier to understand, finding hidden patterns in data, to reading data more accurately and quickly. Thus, the use of visualization techniques on the distribution of drug data at PT. BernoFarm can find out and analyze the trend level of types of drugs, mainstay products, distribution areas, number of distributions of drugs in an area, places and marketing patterns, as well as identify distribution problems quickly and optimally. Several previous studies for the distribution of data usually use the Visual Data Mining (VDM) method from that study, which states that using the Visual Data Mining (VDM) method has the advantage of being able to explore data that has various characteristics and has a large amount of data in the form of a more comprehensive visualization. interesting and easy to understand.